FAKTOR- FAKTOR YANG MEMPENGARUHI MONITORING REAL- TIME PM2.5 DAN CO2 DI AREA TERMINAL BANDAR UDARA: LOW- COST SENSOR, INTERNET OF THINGS (IOT) DAN PENGUKURAN POLUTAN UDARA - Alamsyah, Muhammad; Putra Darsana, Made; Amalia, Direstu; Komalasari, Yeti; Fazal, M. Rafli (Politeknik Penerbangan Surabaya, 2024)
Air pollution poses a serious threat to human health, especially in public areas such as airport terminals. Levels of PM2.5 and CO2 are increasing due to heavy activities and vehicle emissions. This phenomenon is exacerbated by poor air ventilation, constant aircraft movement, an increase in the number of passengers, the use of fossil fuels, and uncontrolled construction and passenger vehicle activities. This article reviews the factors that influence the real-time monitoring of PM2.5 and CO2 at airport terminals, focusing on the use of low-cost sensors and Internet of Things (IoT) technology, as well as air pollutant measurement techniques. The research results indicate that low-cost sensors can provide significant monitoring results, although proper calibration is required to ensure optimal accuracy. The implementation of IoT technology allows for the integration of various sensors into a connected network, increasing efficiency in data collection and analysis. Real-time air pollutant measurements are essential for maintaining air quality in terminal areas, positively impacting the health and comfort of airport visitors and staff. This article concludes that the use of low-cost sensors and IoT technology can enhance the reliability and responsiveness of air quality monitoring systems. The literature review findings affirm that: 1) Low-cost sensors are significant for real-time monitoring of PM2.5 and CO2; 2) IoT is significant for real-time monitoring of PM2.5 and CO2; and 3) Real-time measurement of PM2.5 and CO2 air pollutants is significant for monitoring at airport terminal areas. Keywords: Monitoring real- time, Low- Cost Sensor, Internet of Things, PM2.5, CO2